2015
DOI: 10.1140/epjb/e2014-50772-1
|View full text |Cite
|
Sign up to set email alerts
|

Strong-coupling limit of depleted Kondo- and Anderson-lattice models

Abstract: Fourth-order strong-coupling degenerate perturbation theory is used to derive an effective lowenergy Hamiltonian for the Kondo-lattice model with a depleted system of localized spins. In the strong-J limit, completely local Kondo singlets are formed at the spinful sites which bind a fraction of conduction electrons. The low-energy theory describes the scattering of the excess conduction electrons at the Kondo singlets as well as their effective interactions generated by virtual excitations of the singlets. Bes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…6 the dependence of C na l 1 (ρ i,i+r ) and C na re (ρ i,i+r ) on λ with different α and r. Besides those behaviors observed in Fig. 5, one can observe that when r = 1 and α < 1/8, there are two cusplike minima which are pronounced for C na l 1 (ρ i,i+r ) and are not obvious for C na re (ρ i,i+r ), but they are not critical points of QPTs [53]. In this sense, the SQCs of long-distance spin pairs are more reliable than that of the neighboring spin pair in detecting QPTs of the three-spin interaction XX model.…”
Section: B Transverse-field Xy Modelmentioning
confidence: 61%
See 2 more Smart Citations
“…6 the dependence of C na l 1 (ρ i,i+r ) and C na re (ρ i,i+r ) on λ with different α and r. Besides those behaviors observed in Fig. 5, one can observe that when r = 1 and α < 1/8, there are two cusplike minima which are pronounced for C na l 1 (ρ i,i+r ) and are not obvious for C na re (ρ i,i+r ), but they are not critical points of QPTs [53]. In this sense, the SQCs of long-distance spin pairs are more reliable than that of the neighboring spin pair in detecting QPTs of the three-spin interaction XX model.…”
Section: B Transverse-field Xy Modelmentioning
confidence: 61%
“…Besides the three critical lines, there is a critical line indicated by the minimum of the SQC, but as was shown in Ref. [53], it is not a boundary of QPT.…”
Section: B Transverse-field Xy Modelmentioning
confidence: 76%
See 1 more Smart Citation
“…As a consequence, simulations for this parameter regime become very challenging for DQMC. The dependence of J eff on V has been studied in perturbation theory 66 .…”
Section: Half Depletionmentioning
confidence: 99%
“…In this paper, we study DQPTs following a sudden quench of the Hamiltonian for an extended transverse Ising (ETI) chain [70,71] which incorporates an additional three-spin interaction term in such a way that the spin-chain is still integrable in terms of Jordan-Wigner fermions. The generalized versions of the quantum XY/Ising Hamiltonians have been studied extensively both in the equilibrium [72][73][74][75][76] and non equilibrium [46,77] situations. Remarkably, Zhang et al, [70] showed that the ground states of the Hamiltonian in this model can be represented through loops in a twodimensional auxiliary space spanned by the parameters of the Hamiltonian.…”
Section: Introductionmentioning
confidence: 99%